G553(P) Using Safeguarding Medicals in Place of Separate Initial Health Assessments. (27th April 2016) - Whittington, A; Alison, L; Pearson, L
Abstract : Context: The project involved the safeguarding and looked after children's services of a tertiary children's hospital. The change focused on assessments performed by paediatricians: safeguarding medicals and initial health assessments (IHA) for 'looked after children' (LAC). The clients were children and young people attending safeguarding medicals and who subsequently or concurrently became 'looked after'. Problem: Children entering care may be subject to a safeguarding medical closely followed by an IHA, as per statutory guidance. This could involve two comprehensive health assessments (approximately one hour of clinical time each) resulting in repeat hospital attendances for children, their carers and social workers. Furthermore, the Looked After Children's Health Team (LAACHT) was unable to meet statutory deadlines for assessments, due to the number required. Assessment of problem and analysis of its causes: A 12 month period was selected for analysis and a service evaluation was performed to identify the number of patients attending a safeguarding medical within the preceding three months or one month after becoming 'looked after'. There were 247 patients identified as becoming LAC. Of these, 48 (19%) had a safeguarding medical within the timeframe for an IHA, indicating duplication of work. The remaining LAC did not require a safeguarding medical or it was performed outside the timeframe. Intervention: The safeguarding medical proforma was adapted to consider IHA required items, including the introduction of a questionnaire about the child's mood and favourite activities. Because the safeguarding proforma used at the hospital was already comprehensive, only minor changes were needed to prompt doctors to enquire about educational progress, behaviour, sleep disturbances, diet and dental requirements. The outcome of an IHA is to formulate a health plan hence the safeguarding proforma was adjusted to have a prompt to consider all health needs within the plan. Study design: Service evaluation. Strategy for change: Change was implemented through a scheduled review of the safeguarding proforma. Results were disseminated at the monthly safeguarding team meeting; via email to the team; through the hospital's safeguarding newsletter (distributed to all staff); and on the hospital intranet. The change was immediate but phased in some areas due to a surplus of pre-printed proformas. Measurement of improvement: A further service evaluation will be undertaken to identify if there has been a reduction in IHAs performed following a recent safeguarding medical. In the first month, it is known that at least four children have had a safeguarding medical performed with a view to also using it as an IHA. Effects of changes: The full effects of the changes are yet to be assessed but initial feedback from the safeguarding team is positive. Examples cited include: adding quality to the safeguarding medical; strengthening the way the child's feelings are formally considered; and consideration of wider health needs, including dental. Workload has not perceivably increased. Lessons learnt: There was initial resistance to change within the team and fear of increased workload. This could have been reduced by explaining the rationale for change and involving the whole team earlier in the suggested interventions. A forum for discussion after a pilot period has helped to alleviate anxieties. Lessons learnt include earlier engagement with the team, ensuring their greater ownership and involvement with change. Message for others: Some LAC undergo repeated examinations, some of which could be reduced by combining with other assessments. Other looked after children's services could look at implementing a similar system with their partner safeguarding service in order to use safeguarding medicals in place of a repeated medical for the IHA. This could potentially offer financial savings along with benefits for service users.